Development of nutraceutical tablet from red dragon fruit hylocereus polyrhizus (weber) britton & rose - Abd Manan, Ezzah (2021)
Nutraceuticals are products derived from food sources with added health benefits. They have gained much interest among the public, who take the products to improve and maintain optimal physical and mental conditions. The present study was conducted to characterize nutritional content of Hylocereus polyrhizus, locally known as Buah Naga Merah, and subsequently develop a nutraceutical product that is dietary supplement in the form of tablets with potential medicinal or health benefits. This fruit has become increasingly popular worldwide due to its vitamin and mineral compositions as well as antioxidative properties. Dietary supplement in the form of tablets is accepted and trusted by manufactures and consumers alike thus an ideal way for nutrients and antioxidants to be administered and consume. Water extraction was conducted on fruit pulp and tested on its nutritional composition, chemical constituents, antioxidant properties, mineral and heavy metal contents and cytotoxicity. Nutritional composition was measured using proximate analyses which consists of ash, crude protein, crude fiber, moisture content and pH, while, chemical constituents were determined using Gas Chromatography-Mass Spectrometry (GC-MS). Antioxidant properties were tested using eight different antioxidant in-vitro models namely Total Phenolic Content (TPC), Total Flavonoid Content (TFC), Betacyanin Content (BC), 2,2-diphenyl-1-picrylhydrazyl (DPPH) Radical Scavenging Activity, 2,2'-azino-bis (3-ethylbenzothiazoline-6 sulfonic acid) (ABTS) Radical Scavenging Activity, Ferric Reducing Antioxidant Power (FRAP), β-Carotene Bleaching (β-CB) and Phosphomolybdate Assays (PA). Inductively Coupled Plasma-Mass Spectrometry (ICP-MS) were used to evaluated the metal and heavy metal contents while cytotoxicity activity was examined using Brine Shrimp Lethality Bioassay (BSLB). In the formulation of H. polyrhizus tablets, five variables were studied namely magnesium stearate (0.2 – 1% w/w), menthol (0.2 – 1% w/w), lemon powder (1 – 10% w/w), maltodextrin (5 – 10% w/w) and glucose (37.5 – 53.1% w/w). The effects of components variables on the hardness of tablets were analyzed using a D-Optimal Mixture Experimental Design (D-Optimal MED) statistical software. Results of proximate analyses showed that water extract of the pulp had 0.67±0.02 g/100g ash, 1.39±0.01 g/100g crude protein, 1.82±0.06 g/100g crude fiber, 87.52±0.07 g/100g moisture and pH value of 4.7. No fat constituent was detected. Chemical constituents of pulp showed that the volatile pattern was due to by-products of sugar degradation and Maillard reactions. TPC, TFC and BC were recorded at 32.90±0.92 mg GAE/100mL, 2.26±0.14 mg QE/100mL and 18.21±2.51 mg/100mL of extract, respectively. Free radical scavenging activity, that is DPPH and ABTS protocols, were 73.38±2.24% and 92.66±0.22%, respectively. FRAP, β-CB and PA recorded values of 132.17±3.74 μmol Fe2+/100ml, 74.41±4.84% and 28.94±0.83 mg AAE/100mL of extract, respectively. Metal and heavy metals data of the pulp were compared with the maximum admissible limit in drinking water by World Health Organization (WHO) and all elements investigated were below the acceptable limit suggesting that the fruit is non-toxic. The pulp also displayed no cytotoxicity activity, indicating that the fruit is safe for consumption. In the tablet formulation, D-Optimal MED gave predicted hardness of tablet at 8.5 kg/cm2. The optimal inputs were established as follows: magnesium stearate (0.66% w/w), menthol (0.74% w/w), lemon powder (6.15% w/w), maltodextrin (7.61% w/w) and glucose (44.34% w/w), with the actual hardness of the optimized tablet recorded at 8.581 kg/cm2. The study demonstrated the potentiality of H. polyrhizus as a dietary supplement with therapeutic properties for general consumers well-being.